Fuzzy synchronization of chaotic systems via intermittent control. (January 2018) - Wang, Yuangan; Yu, Honglin
Highlights: Combining with intermittent control method, we propose a fuzzy method to realize synchronization of chaotic system. Based on the method, we establish two plant rules of intermittent control, and get a fuzzy synchronization scheme. Finally, a simulation example is proposed to verify the effectiveness of our results. Abstract: In this paper, a fuzzy method is combined with intermittent control method to realize synchronization of chaotic system. Two plant rules of intermittent control are considered to get two theorems. Fuzzy scheme for synchronization is proposed in theorem. Finally, a simulation example is proposed to verify the effectiveness of our results.